Systematic Literature Review: Peran Pelatihan dan Pengembangan Sumber Daya Manusia (SDM) dalam Meningkatkan Kinerja Karyawan - Nur Hidayah Selviyanti; Nurul Fadila; Yuliana Dewi Sulis; Isa Anshori; Helmi Buyung Aulia Safrizal (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Abstract HR training and development is an important component in the sustainability of an organization or company. This research aims to analyze the role of HR training and development in improving employee performance. The research method used is the systematic literature review method. The analysis technique used is bibliometric data with the help of VosViewer 1.6.1.9 software. The results of the literature review show that HR training and development has a positive impact in improving employee performance. It can be concluded that HR training and development is relevant to be implemented by organizations or companies to improve employee performance skills, capabilities and productivity. The implications of this research include the importance of training and development programs with individual needs and company strategy.